HUBUNGAN INTENSITAS PENGGUNAAN GAWAI TERHADAP PERKEMBANGAN BAHASA ANAK USIA 5-6 TAHUN - Ifa Nur Janah; Een Yayah Haenilah; Fadilah, Chairany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language development is one of the most important aspects of early childhood growth, as it plays a significant role in communication skills and social interaction. However, in practice, there are still children who experience delays or suboptimal language development. One of the factors presumed to influence this condition is the increasing intensity of gadget use among early childhood. This study aims to determine the effect of the intensity of gadget use on the language development of children aged 5–6 years. This study employed a quantitative approach with a correlational method and a descriptive design. The population consisted of 65 children from classes B1, B2, and B3, and the sampling technique used was total sampling. Data were collected through questionnaires distributed to parents and observations of children's language abilities, and then analyzed using the Pearson Product Moment correlation test. The results showed that there is a relationship between the intensity of gadget use and the language development of children aged 5–6 years. Based on these findings, it can be concluded that the intensity of gadget use has an influence on early childhood language development.